ALK rearrangement-associated renal cell carcinoma morphologically mimicking mucinous tubular and spindle cell carcinoma: a case report - Keita Kai; Shohei Tobu; Shinichi Kido; Shuji Mikami; Kengo Takeuchi; Akito Dobashi; Yuki Togashi; Mitsuru Noguchi; Shinichi Aishima (BMC, 2022)
Abstract Background Anaplastic lymphoma kinase rearrangement-associated renal cell carcinoma (ALK-RCC) is an extremely rare tumor and ALK-RCC that mimics mucinous tubular and spindle cell carcinoma (MTSCC) has been very reported only in one instance. Case presentation A 42-year-old Japanese woman was admitted to our hospital for the treatment of a left renal tumor measuring 5 cm in maximum dimension. She underwent a laparoscopic left nephrectomy. Histologically, the tumor formed tubular or focally papillary structures with a small amount of spindle-shaped tumor cells against the background of prominent extracellular mucin. Although the tumor cells were negative for immunohistochemistry (IHC) of alpha-methylacyl-CoA racemase (AMACR) and lymph node metastasis was presented (these are atypical findings for MTSCC), we initially diagnosed the tumor as MTSCC based on its morphological characteristics with mucin deposition. However, an additional IHC analysis revealed that the tumor cells were diffusely positive for ALK-IHC. In addition, TPM3 exon 8 - ALK exon 20 fusion gene was detected by RNA sequencing. The tumor was thus correctly diagnosed as ALK rearrangement-associated renal cell carcinoma (ALK-RCC). Conclusions Since the use of molecular targeted therapy with an ALK inhibitor for ALK-RCC is promising, the correct pathological diagnosis of ALK-RCC is quite important. We strongly recommend that ALK-IHC be routinely performed for renal tumors with negative AMACR staining that mimic MTSCC.